Infection and tissue distribution of highly pathogenic avian influenza A type H5N1 (clade 2.3.4.4b) in red fox kits (Vulpes vulpes) - Brittany D. Cronk; Leonardo Cardia Caserta; Melissa Laverack; Rhea S. Gerdes; Kevin Hynes; Cynthia R. Hopf; Melissa A. Fadden; Shotaro Nakagun; Krysten L. Schuler; Elizabeth L. Buckles; Manigandan Lejeune; Diego G. Diel (Emerging Microbes and Infections, 2023)
Avian influenza H5N1 is a highly pathogenic virus that primarily affects birds. However, it can also infect other animal species, including mammals. We report the infection of nine juvenile red foxes (Vulpes vulpes) with Highly Pathogenic Avian Influenza A type H5N1 (Clade 2.3.4.4b) in the spring of 2022 in the central, western, and northern regions of New York, USA. The foxes displayed neurologic signs, and examination of brain and lung tissue revealed lesions, with brain lesions ranging from moderate to severe meningoencephalitis. Analysis of tissue tropism using RT-PCR methods showed a comparatively lower Ct value in the brain, which was confirmed by in situ hybridization targeting Influenza A RNA. The viral RNA labelling was highly clustered and overlapped the brain lesions, observed in neurons, and grey matter. Whole viral genome sequences obtained from the affected foxes were subjected to phylogenetic and mutation analysis to determine influenza A clade, host specificity, and potential occurrence of viral reassortment. Infections in red foxes likely occurred due to preying on infected wild birds and are unlikely due to transmission between foxes or other mammals.